Effectiveness Of Giving Soy Milk To The Duration Of First Stage Of Labor - Susanti Tria Jaya; Nurin Fauziyah; Suhariati Suhariati (Universitas STRADA Indonesia, 2019)
Soy milk contains phytoestrogens which is the class of isoflavones which have estrogen-like activity. Phytoestrogens have estrogenic activity which ultimately increases uterine sensitivity. This study was to analyze the effectiveness of giving soy milk to the duration of first stage of labor.The results showed that respondents in the treatment group had a duration of fast delivery by 9 people (90%) in the normal category, namely 1 respondent (10%), the majority of the control group respondents in the fast category were 1 respondent (10%), the normal category were 3 respondents (30%) and the slow category were 6 respondents (60%). The Result of analyzing by Mann-Whitney test was found that there was an effect of soy milk giving on the duration of labor (Sig. (2-tailed) of 0,000 <0.05 (α value), so Ho was rejected. Pregnant women can consume soy milk to increase maternal power in labor to advance the duration of labor